OC-092 Impact of colorectal cancer primary node status on survival following colorectal liver metastases resection. (22nd June 2015) - Pathak, S; AlDuwaisan, A; Moore, L; Dhawan, G; Toogood, GJ
Abstract : Introduction: Overall survival for primary colorectal cancer (CRC) is known to be correlated with primary stage (Duke's classification), though the effect of primary disease stage once metastatic spread has occurred needs defining. Primary tumour lymph node status has been previously postulated to negatively impact survival following colorectal liver metastases (CLRM) resection. 1 The objective of the study was to determine the relation between primary CRC node status and survival (disease free survival [DFS] and overall survival [OS]) for patients undergoing hepatic resections for CRLM. Method: Data was collected from a prospectively maintained database of patients undergoing hepatectomy for CRLM between 1 January 2005 and 31 December 2012. Patient demographics, primary CRC staging, operative details, pathology, recurrence and survival data were collected. Primary staging was assessed using the TNM and Dukes grading system, with Dukes A and B classed as node negative, and Dukes C classified as node positive. OS and DFS were analysed using Kaplan-Meier survival curves and log-rank tests. Results: The study included 866 patients, with a mean age of 66 years [23–91]. Of the sample population, 65.8% were male. Of these, 743 patients had primary tumour staging data available. Patients with node negative primary tumours (Dukes A and B) had a significantly longer OS than patients with node positive disease [Dukes C] (median OS 68 vs 43 months, χ 2 p = 0.002). Patients with node negative primaries also had a significantly longer DFS than patients with node positive disease (median DFS 20 vs 16 months, χ 2 p = 0.002). Conclusion: Patients with CRLM who have a Dukes C primary colorectal tumour have a shorter OS and are likely to re-occur earlier post liver resection than those with node negative primary cancer (Dukes A and B). There may be merit in stratifying follow up post CRLM resection, in view of likelihood of recurrent disease. Disclosure of interest: None Declared. Reference: Tomlinson J, Jarnagin W, DeMatteo R, et al . Actual 10-year survival after resection of colorectal liver metastases defines cure. J Clin Oncol. 2007;25(29):4575–4580